A comparative computationally study about the defined m(II) pincer hydrogenation catalysts (m = fe, ru, os). Issue 2 (17th May 2015) - Jiao, Haijun; Junge, Kathrin; Alberico, Elisabetta; Beller, Matthias
Abstract : The mechanism of acetonitrile and methyl benzoate catalytic hydrogenation using pincer catalysts M(H)2 (CO)[NH(C2 H4 P i Pr2 )2 ] (1M ) and M(H)(CO)[N(C2 H4 P i Pr2 )2 ] (2M ) (M = Fe, Ru, Os) has been computed at various levels of density functional theory. The computed equilibrium between1Fe and2Fe agrees perfectly with the experimental observations. On the basis of the activation barriers and reaction energies, the best catalysts for acetonitrile hydrogenation are1Fe/2Fe and1Ru/2Ru, and the best catalysts for methyl benzoate hydrogenation are1Ru/2Ru . The best catalysts for the dehydrogenation of benzyl alcohol are1Ru/2Ru . It is to note that the current polarizable continuum model is not sufficient in modeling the solvation effect in the energetic properties of these catalysts as well as their catalytic properties in hydrogenation reaction, as no equilibrium could be established between1Fe and2Fe . Comparison with other methods and procedures has been made. © 2015 Wiley Periodicals, Inc. Abstract : DFT studies on the defined pincer‐type catalysts M(H)2 (CO)[NH(C2 H4 P i Pr2 )2 ] (1M ) and M(H)(CO)[N(C2 H4 P i Pr2 )2 ] (2M ) (M = Fe, Ru, Os) reveal remarkable differences in electronic structures and hydrogenation reactivity of nitriles, ester, and ketones. For acetonitrile hydrogenation, Fe‐ and Ru‐based catalysts are best. For methyl benzoate hydrogenation and dehydrogenation of benzyl alcohol, Ru‐based catalysts are best. In contrast, Os‐based catalysts are least active.